Measurement and Partitioning of Evapotranspiration for Application to Vadose Zone Studies. Issue 13 (18th January 2018) - Anderson, Ray G.; Zhang, Xudong; Skaggs, Todd H.
Abstract : Core Ideas: Partitioned evaporation and transpiration is important for validating vadose zone models. New partitioning approaches overcome spatiotemporal limitations of previous methods. Some techniques can be applied to existing data to increase E and T observations. Intercomparisons of approaches at a variety of field sites are needed to better assess each approach. Partitioning evapotranspiration (ET) into its constituent components, evaporation ( E ) and transpiration ( T ), is important for numerous hydrological purposes including assessing impacts of management practices on water use efficiency and improved validation of vadose zone models that parameterize E and T separately. However, most long‐established observational techniques have short observational timescales and spatial footprints, raising questions about the representativeness of these measurements. In the past 15 yr, new approaches have allowed ET partitioning at spatial scales ranging from the pedon to the globe and at long timescales. In this update, we review some recent methodological developments for partitioning ET. These include micrometeorological approaches involving the flux variance partitioning of high‐frequency eddy covariance observations and proxies for photosynthesis and transpiration such as measurements of isotopic fractionation and carbonyl sulfide uptake. We discuss advances in partitioning the energy balance between canopy and soil using remote sensing. We conclude that the flux variance partitioning with raw eddy covariance data and the two‐source energy balance approaches with remote sensing platforms may have the greatest potential for partitioning ET, in part because large public repositories of eddy covariance and satellite data could be readily reprocessed to partition ET.